OBERIU’s Absurd Object and the Poetics of Daniil Kharms - Camelia Dinu (eSamizdat, 2023)
By the 1920s the Russian avant-garde was played out, various branches of the artistic movement achieved a balance of power, and leading organizations shifted in favour of the ideological and utopian recipes imposed by the Soviet state. In this monopolizing Soviet cultural context, the group OBĖRIU appeared, reconstituting remnants of the avant-garde and anticipating the modern European poetics of the absurd and surrealism. The first part of the study analyzes the OBĖRIU manifesto and its most important concepts: ‘real art’, ‘the artistic word’, and ‘the artistic object’, and relates them to the literature of the absurd as well as some elements related to the surrealist vision. The second part demonstrates, first, to what degree OBĖRIU principles are recognizable in the work of Daniil Kharms, the founder of the group, and second, to what degree the concept of ‘the artistic object’ in the theory and practice of Kharms reflects a dimension of the art of the absurd, which appears toward the end of the 1920s within the context of the semiotic experiments of the late Russian avant-garde.